Left parathyroid adenoma with features of brown tumor, incidental finding: a case report - Bhandary, Disha; Suvarna, Rithin; Bhandary, Bhaskara (International Surgery Journal, 2021)
Primary hyperparathyroidism (PHPT) occurs in a setting of excessive parathyroid hormone (PTH) secretion with an autonomous parathyroid gland which resulting in hypercalcemia. Cases of parathyroid adenoma are rare, PTH is a chief regulator of calcium homeostasis in the human body. PHPT could be caused by solitary adenomas, hyperplasia, multiple adenomas and carcinomas. A 35-year-old female who came in with complaints of left hip pain past 1 month which aggravated since 1 week, with previous medical history of hyperthyroidism. Laboratory and biochemical findings suggested features of PHPT. She underwent left parathyroid excision with subtotal thyroidectomy. Histopathology analysis revealed features of parathyroid adenoma with eosinophilic to clear cytoplasm, few foci with oxyphilic nodules. Patient showed significant fall in PTH levels after tumor excision and is being discharged 5th day after surgery. PHPT occurs at any age, but it is most commonly seen in people over the age of 50 years and postmenopausal women. The current presentation of PHPT shifts from the classical symptomatic form to the asymptomatic form. parathyroidectomy is still the treatment of choice for both symptomatic and asymptomatic forms. Parathyroid adenoma has an excellent prognosis with surgical treatment.